2019
DOI: 10.1002/jbio.201900136
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of microenvironment characteristics and metabolic activity in glioma via multiphoton microscopy

Abstract: Tumor microenvironment and metabolic activity in gliomas are the important biomarkers to evaluate the progression of gliomas. Many evidences have suggested that the targeting of metabolic activity and tumor microenvironment simultaneously can be more effective to take the tumor therapy. Therefore, the noninvasive, accurate assessment of tumor microenvironment and metabolic activity is quite important in clinical practice. Multiphoton microscopy (MPM), based on two‐photon‐excited fluorescence and second harmoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Previous reports have shown increased NADH content in tumors 32 , 33 . Our previous studies on normal and glioma human brain tissues also demonstrated higher NADH levels in gliomas 34 . In this study, when the dura mater was invaded by tumor cells, the metabolic activity increased, which explains the higher NADH content in the meningioma-infiltrated dura mater.…”
Section: Discussionsupporting
confidence: 65%
“…Previous reports have shown increased NADH content in tumors 32 , 33 . Our previous studies on normal and glioma human brain tissues also demonstrated higher NADH levels in gliomas 34 . In this study, when the dura mater was invaded by tumor cells, the metabolic activity increased, which explains the higher NADH content in the meningioma-infiltrated dura mater.…”
Section: Discussionsupporting
confidence: 65%
“…Previous studies have demonstrated that that multiphoton excitation of autofluorescence hold the potential to distinguish tumor tissue and normal brain based on the intensity and lifetime of fluorescence 10 , 11 . Some microenvironment characteristics in gliomas, such as collagen deposition in extracellular matrix and tumor angiogenesis, were identified in the MPM images for the brain slices after frozen cutting previously 14 , 15 . We found that MPM provides structural information similar to that of the co-located histopathology for fresh brain tissues.…”
Section: Discussionmentioning
confidence: 99%
“…To improve intraoperative assessment, various optical techniques have been developed for rapid, high-resolution imaging of fresh human brain tissues, including microscopy with ultraviolet surface excitation (MUSE) 5 , light-sheet microscopy (LSM) 6 , optical coherence tomography (OCT) 7 , stimulated Raman scattering (SRS) microscopy 8 , 9 , and multiphoton microscopy (MPM) 10 - 15 . For MUSE and LSM, fluorescent dyes are required and tissue must be rinsed prior to imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Several algorithms for 2D segmentation have been proposed: The Otsu thresholding procedure to maximize the intra-class variance of segmented areas along with mathematical morphology to filter noise and unreliable data, as well as Fuzzy C-means and graph cuts in LAB colorspace [199].…”
Section: Application Of Machine Learning To Increase the Sensitivity Of Detection Methods For Glioma Molecular Markersmentioning
confidence: 99%